Projection of Future Summer Precipitation over the Yellow River Basin: A Moisture Budget Perspective - Jiao Li; Yang Zhao; Zhenfei Tang (Atmosphere, 2020)
The projection of future precipitation over the Yellow River Basin (YRB) is of great importance to regional climate change adaptation and mitigation. Using the historical simulations and projections under the four combined scenarios of the shared socioeconomic pathways and the forcing levels of the Representative Concentration Pathways (SSP1-2.6, SSP2-4.5, SSP3-7.0 and SSP5-8.5) provided by the multimodel ensemble mean of 10 models in phase six of the Coupled Model Intercomparison Project (CMIP6), the projected spatial and temporal changes of future summer precipitation over the YRB and the possible physical mechanisms underlying future summer precipitation changes are investigated. Large discrepancies in precipitation exist among the four scenarios during the latter half period of the 21st century, with precipitation under SSP5-8.5 being the largest. Nevertheless, the precipitation under each of the four scenarios shows a similar spatial pattern over the YRB, with an east–west-oriented gradient. A comparison of projected moisture transport into the YRB among the four scenarios reveals two channels (westerlies and monsoon flow) under SSP5-8.5, whereas the monsoon flow from adjacent oceans is important under the other three scenarios. Further analysis of the unique features of the projected moisture flux and substantial increase in summer precipitation under SSP5-8.5 indicates that the future summer precipitation trend over the YRB can be mainly attributed to an increase in evaporation and moisture advection.